Revision of Fedekurtzia (pteridosperm) and allied fronds from the Carboniferous of Gondwana - ELIANA P. COTUREL; SILVIA N. CÉSARI (Acta Palaeobotanica)
Carboniferous foliage of Fedekurtzia argentina (Kurtz) Archangelsky from Gondwana is systematically described and revised. The frond is reconstructed based on specimens of the late Serpukhovian–Bashkirian Nothorhacopteris/Botrychiopsis/Ginkgophyllum flora of western Argentina, especially from the Jejenes, Tupe and Volcán formations. The whole-frond reconstruction emphasizes the variation in pinnule shape throughout the basal, medial and distal sections of the frond. The basalmost rachis possesses cyclopteroid pinnules grading to pinnae with obovate to wedge-shaped pinnules at the medial section of the frond. Distal pinnae are shorter, bearing imbricate and more dissected pinnules. Specimens from the same type locality from which F. argentina comes, previously assigned to Triphyllopteris cuyana Leguizamón & Vega, are reassigned to F. argentina, as well as ovuliferous and microsporangiate structures in organic connection. Two decades ago a revision of the German Triphyllopteris genus rejected T. cuyana as representative of the taxon, and the Argentinian specimens remained as indeterminate “triphyllopteroid” fronds. The ovulate organ Polycalyx Vega & Archangelsky is considered to be in organic connection with vegetative fragments of F. argentina, and its cupulate character is discussed. Pollen organs represented by multi-forked axes bearing fusiform sporangia of Rinconadia Vega are also in organic attachment and included in the Fedekurtzia argentina reconstruction. The pollen or prepollen grains are trilete and with granulate sculpture. The paper presents a comparison with Botrychiopsis weissiana Kurtz emend. Archangelsky & Arrondo, which differs in its rounded and entire-margin pinnules. Similar specimens from Australia formerly described as Rhacopteris, Sphenopteridium and Archaeopteris and currently included in Fedekurtzia intermedia Rigby share morphological characters with the Argentinian species. A revision of the Australian material is necessary to confirm synonymy. Fedekurtzia belongs to the pteridosperms based on the reproductive organs and is here assigned to Austrocalyxaceae. Its reconstruction now constitutes one of the most complete seed-ferns known from the Carboniferous of Gondwana.